2016
DOI: 10.1371/journal.pone.0168147
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Disturbances in Adult-Onset Still’s Disease Evaluated Using Liquid Chromatography/Mass Spectrometry-Based Metabolomic Analysis

Abstract: ObjectiveLiquid chromatography/mass spectrometry (LC/MS)-based comprehensive analysis of metabolic profiles with metabolomics approach has potential diagnostic and predictive implications. However, no metabolomics data have been reported in adult-onset Still’s disease (AOSD). This study investigated the metabolomic profiles in AOSD patients and examined their association with clinical characteristics and disease outcome.MethodsSerum metabolite profiles were determined on 32 AOSD patients and 30 healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Recent studies have been proposed to identify metabolites in clinical research using LC‐MS to determine correlations with diseases. This technique is widely used for a sensitive and noninvasive diagnostic for metabolomic research [27,28,46].…”
Section: Analytical Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have been proposed to identify metabolites in clinical research using LC‐MS to determine correlations with diseases. This technique is widely used for a sensitive and noninvasive diagnostic for metabolomic research [27,28,46].…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…Eighteen different expressed metabolites were identified in this disease by LC‐MS‐based analysis, of which 13 were validated by NMR/MS. One of such metabolites was UCA, which was found to have significantly lower serum levels [28].…”
Section: Analytical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] Among the analytical methods used in metabolomics research, liquid chromatography/ mass spectrometry (LC/MS) has been shown to be one of the best techniques in terms of selectivity, sensitivity, and reproducibility. [40,41] It provides the highest level of metabolite coverage, using a unified analytical technique. In LC-MS, limit of sensitivity is about 5nM to10nM and the number of detectable characteristics -from 5000 to 20000.…”
Section: Heart Type Of Tcmentioning
confidence: 99%
“…[42] Measuring the Glu concentration by MRS with the usual values of the magnetic field causes difficulty in distinguishing between Glu and Gln; for this reason, a composite index is often used. [43] Another aspect of modern metabolomic research is the application of multivariate statistical analysis [40] and the construction of predictive models. [30] Thus, the levels of metabolites in the blood plasma reflect the systemic reactions of the body and are considered as a body's response to the disease.…”
Section: Heart Type Of Tcmentioning
confidence: 99%